El nivel socioeconómico para el desarrollo de la inteligencia cognitiva en niños de preparatoria, escuela de educación básica teniente Hugo Ortiz, ciudad de Loja, periodo 2018-2019. - Aguirre Jaramillo, Paola Kamila (2019)
The title of this investigation is: THE SOCIOECONOMIC LEVEL FOR THE DEVELOPMENT OF COGNITIVE INTELLIGENCE OF FIRST GRADE CHILDREN ATTENDING LIEUTENANT HUGO ORTIZ ELEMENTARY SCHOOL, LOJA; FROM 2018 TO 2019. The general objective was: Identify how the socioeconomic level influences the development of cognitive intelligence of first grade children attending, Lieutenant Hugo Ortiz Elementary, Loja; from 2018 to 2019, the methods used in this investigation were: descriptive, inductive, synthetic, deductive, analytical; the instrument used was the observation, a survey administered to parents and aimed to categorize at what socioeconomic level first grade children are; also, the Raven test was used to verify what the children's cognitive intelligence is. It was possible to collect verified data about the socioeconomic level and deficiencies that children present during the development of cognitive intelligence. The most relevant results obtained through the instruments applied to the total population of 44, disaggregated into 22 parents and 22 boys and girls, are: the Raven test showed that 36% of children investigated had a satisfactory IQ while 64% unsatisfactory. With the design and application of the change proposal, it was able to improve children’s intelligence through didactic games; the results achieved were that 77% of the children investigated reached very satisfactory IQ, while 33% of the children got unsatisfactory. Therefore, it is concluded that the socioeconomic level does not affect the development of cognitive intelligence entirely, but it depends on the management and strategies that the teacher applies on to impart knowledge to her/his students. The didactic games are very relevant, they benefit parents and children, help to understand the world around them and are necessary to interact with more individuals.